Comparison of some economic traits by genetic cluster of Aberdeen Angus cattle - J. Márton; S. Bene; I. Anton; A. Zsolnai; F. Szabó (Archives Animal Breeding)
The Angus cattle population of Hungary was categorized into four groups using 12 microsatellite markers exhibiting notable genetic variations. Moreover, some traits influencing the profitability and sustainability of beef cattle farming were compared between groups. Data were obtained from 5075 cows (born between 1990–2020) and 19 142 calves (born between 1997–2023), including 10 629 bull calves and 8513 heifer calves of different genetic backgrounds. Genetic groups were distinguished by origin, color, size, and type: blue group (BG), red group (RG), green group (GG), and yellow group (YG). The six investigated traits were age at first calving (AFC), productive lifespan (PL), number of calves born (NCB), culling age (AGE), birth weight (BW), and the 205 d adjusted weaning weight (WW). The averages of the six tested traits were as follows: AFC – 2.35 ± 0.54 years; NCB – 5.89 ± 3.69 heads; PL – 6.85 ± 4.13 years; AGE – 9.2 ± 4.26 years; BW – 29.4 ± 4.28 kg; and WW – 176.9 ± 44.07 kg. YG excelled in terms of NCB, PL, AGE, and WW traits, while RG performed best in terms of AFC and BW. BG displayed the lowest performance across NCB, PL, AGE, BW, and WW. The heavier Red Angus individuals were largely behind the performance of the traditional-type, smaller British-type Black and Red Angus individuals in the tested traits affecting sustainability and profitability. Significant reproduction and longevity trait differences exist among different genetic groups of Angus beef cattle genotyped by DNA microsatellite information. The results indicated significant differences in terms of the performance of different Angus types with regard to the tested traits. These findings could be useful in developing breeding concepts and making selection decisions, contributing to more efficient and sustainable breeding strategies.